Shoeing the Children: The Impact of the TOMS Shoe Donation Program in Rural El Salvador. (20th September 2016) - Wydick, Bruce; Katz, Elizabeth; Calvo, Flor; Gutierrez, Felipe; Janet, Brendan
Abstract: We carry out a cluster-randomized trial among 1, 578 children from 979 households in rural El Salvador to test the impacts of TOMS shoe donations on children's time allocation, school attendance, health, self-esteem, and aid dependency. Results indicate high levels of usage and approval of the shoes by children in the treatment group, and time diaries show modest evidence that the donated shoes allocated children's time toward outdoor activities. Difference-in-difference and ANCOVA estimates find generally insignificant impacts on overall health, foot health, and self-esteem but small positive impacts on school attendance for boys. Children receiving the shoes were significantly more likely to state that outsiders should provide for the needs of their family. Thus, in a context where most children already own at least one pair of shoes, the overall impact of the shoe donation program appears to be negligible, illustrating the importance of more careful targeting of in-kind donation programs.